Teripang, Sea Cucumber (Stichopus sp.) Fractions Induce Apoptosis in Liver Cancer Cell Line (HepG2) - Yosie Andriani; Murni Nur Islamiah Kassim; Efriyana Oksal; Rosmiati Rosmiati; Kamariah Bakar; Nur Asniza Aziz; Desy Fitrya Syamsumir; Alifah Husnun Kholieqoh; Yeong Yik Sung; Purbowatiningrum Ria Sarjono; Dwi Hudiyanti; Tengku Sifzizul Tengku Muhammad (Marine Science Department Diponegoro University, 2026)
Cancer remains a major global health problem, prompting continuous exploration of marine organisms as sources of novel bioactive compounds. This study evaluated the cytotoxic and apoptosis-inducing activities of F9 and F10 fractions obtained from methanolic extracts of sea cucumber (Stichopus sp.) against the human hepatocellular carcinoma cell line HepG2 as an in vitro cancer model. Sea cucumber samples were extracted using methanol maceration and subsequently fractionated through Medium Pressure Liquid Chromatography (MPLC) to obtain bioactive fractions. Cytotoxic activity was assessed using the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay after 24, 48, and 72 h of incubation to determine cell viability. Apoptotic effects were examined using Annexin V and propidium iodide (PI) staining, followed by fluorescence microscopy to evaluate morphological changes associated with apoptosis. The results demonstrated that both fractions exhibited significant cytotoxic effects on HepG2 cells in a time-dependent manner, with IC50 values of 14 µg.ml-1 for the F9 fraction and 23 µg.ml-1 for the F10 fraction after 72 h of treatment. Among the tested fractions, F9 showed stronger cytotoxic activity at lower concentrations. Morphological observations revealed typical apoptotic characteristics such as cell shrinkage, membrane blebbing, nuclear condensation, and phosphatidylserine externalization, indicating apoptosis as the predominant mechanism of cell death. These findings demonstrate that Stichopus sp. contains bioactive compounds with anticancer potential. This study highlights the importance of marine invertebrates as natural resources for biomedical applications and supports the development of marine biotechnology strategies for cancer therapy. Further investigations are needed to identify the active compounds responsible and clarify their molecular mechanisms of action.